Differential Sensitivity of Fruit Pigmentation to Ultraviolet Light between Two Peach Cultivars - Zhao, Yun; Dong, Weiqi; Wang, Ke; Zhang, Bo; Allan, Andrew C.; Lin-Wang, Kui; Chen, Kunsong; Xu, Changjie (Frontiers in Plant Science, 2017)
Anthocyanins provide nutritional benefits and are responsible for red coloration in many fruits. Light affects anthocyanin biosynthesis in peach (Prunus persica). However, some cultivars show differential sensitivity to light. In the present study, ‘Hujingmilu (HJ)’, a naturally deeply colored cultivar, and ‘Yulu (YL)’, showing low pigmentation, were used to study the mechanism underlying UV-light-induced anthocyanin biosynthesis. Both UVA and UVB induced fruit pigmentation of ‘HJ’, but ‘YL’ was only sensitive to UVB. Transcriptomic analyses showed over 5000 genes were differentially expressed by pairwise comparisons of RNA libraries isolated from tissue of each cultivar treated with darkness, UVA and UVB. Twenty-three genes related to anthocyanin biosynthesis were identified from the transcriptome data, which were coordinately up-regulated during accumulation of anthocyanins, and down-regulated in the dark. Altered expression of several light receptors, as well as CONSTITUTIVE PHOTOMORPHOGENIC10 (COP10) and ELONGATED HYPOCOTYL 5 homolog (HYH), and a specific anthocyanin transporter glutathione S-transferase (GST), in ‘YL’ fruit appears to be responsible for the insensitivity to UVA of this cultivar. Expression profiles of several transcription factors of the families MYB, bHLH, bZIP and NAC were highly correlated with those of the anthocyanin biosynthesis genes. The study provides a valuable overview of the underlying molecular mechanisms of UV-light induced anthocyanin response using peach cultivars with differing light sensitivities.